Al-Ghazali: Educators and Students Concepts, and Its Implications for Education in Indonesia - M. Fahmi Maulana; Septian Kurnia Sari; Rahmad Alim Witari; Aisha Zerlina Syahda (ISTAWA, 2021)
Islamic education is a medium to make perfect human beings and have the ability to know and obey their God. The essence of Islamic education is an interaction of two components of education, namely educators and students. This research aims to determine the concept of educators and students from the perspective of Al-Ghazali and its implications for education in Indonesia. To achieve this goal, the researcher uses the literature study method by examining data sources from books, scientific journals, and research reports which are then used to identify the concepts of educators and students. The results of this study indicate that the concept of educator according to Al-Ghazali not only provides knowledge but also provides moral development and straightens the behavior of students with Islamic teachings. Meanwhile, according to Al-Ghazali, the concept of students is human nature, so they need guidance to meet their needs.